Exfoliation in Endotoxin‐Free Albumin Generates Pristine Graphene with Reduced Inflammatory Properties. Issue 12 (17th September 2018) - Lebre, Filipa; Hanlon, Damien; Boland, John B.; Coleman, Jonathan; Lavelle, Ed C.
Abstract: Graphene‐based materials are under consideration as a new generation of biomaterials for medical applications, owning to their distinctive physicochemical properties. A major obstacle to clinical translation of novel biomaterials is the presence of residual endotoxin contaminants that can trigger deleterious inflammatory responses and unrelated immunomodulatory effects. To overcome this challenge, a liquid exfoliation methodology to prepare endotoxin‐free bovine serum albumin (BSA)‐exfoliated pristine graphene (EF‐Gr) was developed and compared with conventional BSA‐exfoliated graphene (C‐Gr) and sodium cholate‐exfoliated graphene (SC‐Gr). In contrast to SC‐Gr, protein‐exfoliated graphene exhibits low toxicity. Moreover, BSA‐exfoliated EF‐Gr does not trigger cytokine secretion or increase costimulatory molecule expression in dendritic cells (DCs) or macrophages; however it retains the ability to activate the NLRP3 inflammasome in DCs primed with Toll‐like receptor (TLR) agonists. The results suggest that some reported immunostimulatory effects of graphene preparations may have resulted from contaminants in the formulations. When injected into mice, the inflammatory response induced is comparable in magnitude to that induced by the safe and effective vaccine adjuvant alum. Overall, the study demonstrates the feasibility of producing endotoxin‐free pristine graphene that facilitates assessment of the potential of pristine graphene for novel biomedical applications without the confounding effects of toxic and inflammatory contaminants. Abstract : This study reports the production of endotoxin‐free bovine serum albumin (BSA)‐exfoliated pristine graphene (EF‐Gr) and its capacity to modulate immune cell responses. While conventional BSA‐exfoliated graphene induces unspecific immunomodulatory responses, the same is not observed with EF‐Gr. This suggests that previously reported effects of graphene preparations might have resulted from contaminants and calls for a reassessment in the literature.